Indonesia Website-Based Digital Audio-Visual Storytelling Media for Children Aged 5–6 Years - Setyatmoko, Kristina Madalena; I Made Tegeh; Made Vina Arie Paramita (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
This research is motivated by the lack of engaging and interactive learning media for children aged 5–6 years, particularly in introducing storytelling as part of moral and language education. The aim of this study is to develop website-based digital audio-visual media for storytelling for children aged 5–6 years. This development research employs the ADDIE model. Data collection was carried out using questionnaire sheets to measure the validity and acceptability of the media from various aspects. Data analysis was conducted by calculating the percentage of validity provided by experts and respondents. The results of the study show that the Website-Based Digital Audio-Visual Media was rated highly valid by subject matter experts (89.75%) and media experts (88.75%). Teacher and child respondents also gave very high ratings, with an average of 95%. Overall, it can be concluded that the website-based digital audio-visual media for storytelling for children aged 5–6 years is not only valid and effective but also highly beneficial in increasing children's interest in storytelling-based learning. The implication is that this media can serve as a valuable reference in the broader development of interactive learning tools, especially for early childhood education.